Time Operators Determined by Cylindrical Processes - Suchanecki, Zdzislaw (Frontiers in Physics, 2020)
The main purpose of this paper is to study time operators associated with cylindrical elements, i.e. generalized functions with values in locally covex speces. It is given the characterization of the domains of the constructed time operators and partially resolved the problem of decomposability of random elements.